Regulacija in liberalizacija trga poštnih storitev - Rozman, Til (Podjetje in delo, 2018)
This paper addresses regulation of the postal services market in the light of the changing market conditions. Introduction to the topic is followed by the second chapter, which describes the EU regulatory framework. The third chapter challenges key concepts of postal regulation from the perspective of the changing market conditions. 20 years after adoption of the first Directive, it is evident that competition is, on the one hand, weak in the letter market and, on the other hand, well developed in the parcel market. The changing market and years of experiences with the Directive legitimise the following question: Is the Directive still fit for its purpose? Since the scope of the paper does not allow a comprehensive approach, only fragments of the selected contemporary issues are addressed - definition of the universal service, its quality and financing, understanding of the tariff principles and access to the network.
Keywords: dostop do poštnega omrežja; kompenzacijski sklad; nediskriminacija; tarifna načela; univerzalna poštna storitev